A prince among frogs - Baker, E. D. (Baker, E. D. Tales of the frog princess, 2011)
While Princess Millie and her dragon fiance prepare for their wedding, the entire royal family of Greater Greensward teams up to find Millie's baby brother, who has been kidnapped and turned into a frog.